Domestic and sexual violence data collection: A Report to Congress under the Violence Against Women Act - (:unkn) unknown (My University, 2016)
This report, supported by the National Institute of Justice and the Bureau of Justice Statistics, represents an important first step in analyzing what needs to bedone to ensure reliable estimates of the extent and nature of violent crimes committed against women. The study found that the Federal Government and the majority of States currently are collecting some statistics annually on thesecrimes: 35 States collect data on domestic violence, 30 gather statistics on sexual violence. Some of these existing State programs can serve as working models for States that currently do not collect data on these crimes.